Strategi Bertahan Pada Masa Pandemi Covid 19 di Ancak Restaurant - I Gusti Agung Mirah Sanjiwani (Altasia Jurnal Pariwisata Indonesia, 2022)
The Covid-19 pandemic was giving huge impact on tourism business in Bali. These efforts require the proper strategy of the impacts that have been experienced. Ancak Restaurant as one of the restaurants at the Mercure Bali Legian Hotel has been trying to develop a strategy to survive during the pandemic. This study aims to analyze the impact and strategies designed by restaurant management to survive the Covid-19 pandemic. The qualitative approach is carried out by conducting structured interviews and literature studies. Changes has been occurred in operational activities at Ancak Restaurant include operational hours, food portions, employee salaries, laid off of employment and lack of service. The strategy taken by restaurant management to survive during the pandemic is to implement health protocols, regulation in human resources, operational cost savings, and design appropriate promotions. The promotion policy implemented in the restaurant is need to be improved, then in the future it will be more attractive and appropriate to the cost in order to increase number of guest visit to the restaurant.